Association of adoption of transradial access for percutaneous coronary intervention in ST elevation myocardial infarction with door‐to‐balloon time. Issue 2 (27th February 2020) - Huded, Chetan P.; Kapadia, Samir R.; Ballout, Jad A.; Krishnaswamy, Amar; Ellis, Stephen G.; Raymond, Russell; Cho, Leslie; Simpfendorfer, Conrad; Bajzer, Chris; Martin, Joseph; Nair, Ravi; Lincoff, A. Michael; et al.
Abstract: Objectives: We aimed to study adoption of transradial primary percutaneous coronary intervention (TR‐PPCI) for ST elevation myocardial infarction (STEMI) ("radial first" approach) and its association with door‐to‐balloon time (D2BT). Background: TR‐PPCI for STEMI is underutilized in the United States due to concerns about prolonging D2BT. Whether operators and hospitals adopting a radial first approach in STEMI incur prolonged D2BT is unknown. Methods: In 1, 272 consecutive cases of STEMI with PPCI at our hospital from January 1, 2011, to December 31, 2016, we studied TR‐PPCI adoption and its association with D2BT including a propensity matched analysis of similar risk TR‐PPCI and trans‐femoral primary PCI (TF‐PPCI) patients. Results: With major increases in hospital‐level TR‐PPCI (hospital TR‐PPCI rate: 2.6% in 2011 to 79.4% in 2016, p ‐trend<.001) and operator‐level TR‐PPCI (mean operator TR‐PPCI rate: 2.9% in 2011 to 81.1% in 2016, p ‐trend = .005), median hospital level D2BT decreased from 102 min [81, 142] in 2011 to 84 min [60, 105] in 2016 ( p ‐trend<.001). TF crossover (10.3%; n = 57) was not associated with unadjusted D2BT (TR‐PPCI success 91 min [72, 112] vs. TF crossover 99 min [70, 115], p = .432) or D2BT adjusted for study year and presenting location (7.2% longer D2BT with TF crossover, 95% CI: −4.0% to +18.5%, p = .208). Among 273 propensity‐matched pairs, unadjusted D2BT (TR‐PPCI 98 [78, 117] min vs. TF‐PPCI 101 [76, 132] min, p = .304), and D2BT adjusted for study year and presenting location (5.0% shorter D2BT with TR‐PPCI, 95% CI: −12.4% to +2.4%, p = .188) were similar. Conclusions: TR‐PPCI can be successfully implemented without compromising D2BT performance.